Knowledge of Cervical Cancer and Prevention Methods among Women attending Reproductive Child Health Clinics in Tanzania: A Mixed-Method Study (Tanzania Medical Journal, 2025)
Background: Cervical cancer, despite being preventable, is the leading cause of death among women globally, with 10,241 new cases in Tanzania annually causing over 6,000 deaths. Despite the Human papillomavirus (HPV) vaccine as one of the effective strategies for cervical cancer, its uptake remains low. The latter happens amidst a low turnout of women for cervical cancer screening. Altogether, this poses a question of awareness and knowledge of women on cervical cancer prevention methods.Objective: To analyze the awareness of cervical cancer and knowledge of preventive strategies among women of childbearing age in Tanzania.Methodology: A hospital-based mixed-method study was conducted in May 2022 in Ilala municipal council, Dar es Salaam, Tanzania. A total of 404 women of childbearing age participated in a cross-sectional survey, while 46 women participated in six focus group discussions. Stata software 12 was used to analyze quantitative data, while qualitative data were analyzed thematically.Results: Out of the 404 women interviewed, 259 (64.1%) were married, and 196(48.5) had primary education, while the majority 253(62.1%) were aged between 25 – 39 years. The majority, 314 (77.7%), had knowledge of cervical cancer, while 165 (40.8%) knew that cervical cancer is preventable, with only 48 (11.9%) ever been screened, and 21(5.2%) were vaccinated against HPV. Following thematic analysis, participants described how lack of knowledge can lead to fear of screening procedures, fear for diagnosis and worries on the anticipated cervical cancer treatment costs. Limited knowledge of the HPV vaccine is the primary reason for not being vaccinated and preventing their girls from being vaccinated.Conclusion: Most women had the knowledge of the disease but unaware of the main risk factors, HPV infection, and vaccine availability, suggesting the need for frequent health education sessions and support for social and mass media to educate the community.